(untitled) (Journal of the College of Basic Education, 2025)
study aims to know the effect of Driver’s model on the acquisition of Kurdish grammar concepts among eighth grade female students and their attitudes towards it. The study sample consisted of (67) female students, from (W a Fa) School, Chamchamal District, Sulaymaniyah Governorate, for the academic year 2022-2023. It was classified into two groups: control (34) students who studied using the traditional method and experimental (33) students who studied according to Driver’s model. The researcher made an equality between them in terms of (chronological age calculated in months, intelligence test, previous year’s grades in the Kurdish language, previous information), and the researcher prepared two tools for this study. It is (a test in the acquisition of concepts (25) Items and preparing a measure of the attitude towards the subject Consisting of (36) items) After completing the experiment, the two tools were applied to them, and the results showed that the female students of the experimental group outperformed the students of the control group in the test of the acquisition of concepts and the attitude measure.